Image Media To Enhance English Vocabulary Mastery In Fifth Grade Students Of SDN 1 Dara Kunci - Imran, Fathurrahman; Kamarudin, Kamarudin (Jurnal Ilmiah Mandala Education (JIME), 2024)
AbstractThis study aims to describe the use of Picture to Enhance the ability to master English vocabulary of Fifth Grade Students of SDN 1 Dara Kunci for the 2023/2024 school year. In data collection researchers use observation, test and documentation techniques. The data were analyzed in a qualitative descriptive manner. The study was conducted in 2 cycles starting with preliminary studies. During the study, researchers found that in the pre-cycle, the level of students' vocabulary mastery ability was still low, which was 55.8  % in the range of 40% - 55%. In the first cycle after students were given actions using Picture,  the student's ability level increased to 61.5% and entered the medium criteria (56%-75%). In cycle II after students were given actions based on observations in cycle I, students' vocabulary mastery ability increased to 78.3% so that it was included in the high criteria (76%-100%). From the results of the study, it can be concluded that the use of Picture can increase student learning activities and increase vocabulary mastery.